DRUG-RELATED PROBLEMS IN CARDIAC NEONATES UNDER INTENSIVE CARE - Amanda Roseane Farias do Nascimento; Ramon Weyler Duarte Leopoldino; Marco Edoardo Tavares dos Santos; Tatiana Xavier da Costa; Rand Randall Martins
ABSTRACT Objective: To determine the frequency and nature of the Drug Related Problems (DRP) in neonates with cardiac diseases admitted to an Intensive Care Unit. Methods: This prospective cross-sectional study was developed at the Neonatal Intensive Care Unit (NICU) of a teaching maternity hospital in Brazil from January 2014 to December 2016. All neonates diagnosed with any heart disease (congenital heart disease, cardiomyopathy, arrhythmias, etc.) and who were admitted to the NICU for more than 24 hours with at least one prescribed drug were included in the study. Demographic and clinical data were collected from the records of the institution's clinical pharmacy service. DRP and their respective interventions were independently reviewed and classified by two pharmacists. DRP classification was performed through the Pharmaceutical Care Network Europe v6.2 system. Results: 122 neonates were included in the study. The frequency of neonates exposed to DRP was 76.4% (confidence interval of 95% [95%CI] 65.9-82.0), with a mean of 3.2±3.8 cases/patient. In total, 390 DRP were identified, of which 49.0% were related to "treatment effectiveness", 46.7% to "adverse reactions" and 1.0% to "treatment costs". The medicines most involved in DRP were Vancomycin (10.2%; n=46), Meropenem (8.0%; n=36) and Furosemide (7.1%; n=32). Pharmacists performed 331 interventions, of which 92.1% were accepted by physicians and nurses. Conclusions: The study showed that DRP are very frequent in patients with cardiac diseases hospitalized in the NICU, predominating problems related to the effectiveness and safety of the drug treatment.